Cities on the rebound : a vision for urban America - Hudnut, William H., III, 1932-2016 (ULI--The Urban Land Institute, 1998)
Author Bill Hudnut draws on his past experience as mayor of Indianapolis to describe his vision for dealing with diversity, encouraging sustainable development, finding alternatives to sprawl, managing technological change, regional collaboration, improving government efficiency, and more.